Performance of different genotypes of vegetable soybeans in Jaboticabal-SP - Castoldi, R. [UNESP]; Charlo, H. C O [UNESP]; Braz, L. T. [UNESP]; Mendonça, J. L. [UNESP]; Panizzi, M. C C [UNESP]; Ito, L. A. [UNESP] (My University, 2008)
The study was conducted in the field, in the experimental area of the Section of Crop Production and Aromatic Medicinal Plants, belonging to the Faculty of Agricultural and Veterinary Sciences, Jaboticabal Campus-SP. The aim of the study was to assess the performance of seven genotypes of vegetable soybeans in Jaboticabal-SP. The experiment was carried out in a complete randomized block design with seven treatments (genotypes) and four replications. The genotypes examined were: CNPSOI, JLM003, JLM010, JLM018, JLM019, JLM024 and BRS216. The seeds were obtained from EMBRAPA-Soja and EMBRAPA- Hortaliças, and planted in Styrofoam trays with 128 cells containing Plantmax Hortaliças® as substrate. Transplanting occurred 10 d after seeding when the seedlings showed 2 or 3 definitive leaves and about 12 cm in height, demonstrating that the soil had been properly prepared according to the recommendations for this crop. Pests and diseases were adequately controlled in the event of their occurrence in the experimental area and in accordance with technical recommendations for the chemical products utilized. Collections were carried out based on the maturation of the pods, according to the scale of Fehr and Caviness (1977) adapted by Costa and Marchezan (1982), when the pods reached the reproductive stage R6. The parameters determined were mean precocity, height of the first pod, mean number of pods per plant, mean number of seeds per pod, fresh weight of 100 seeds and total yield of immature grains. Based on the results obtained, the genotypes JLM003 and JLM010 were found to be most indicated for growing vegetable soybeans, because of their capacity to produce immature grains of 1090 and 848 g·m-2, respectively, and fresh weights for 100 seeds of 62.20 and 68.19 g, respectively.
Keywords: Edaname; Glycine max; Parameters; Yield; Soja